Delivery of PLGA-Loaded Influenza Vaccine Microparticles Using Dissolving Microneedles Induces a Robust Immune Response - Emmanuel Adediran; Tanisha Arte; Dedeepya Pasupuleti; Sharon Vijayanand; Revanth Singh; Parth Patel; Mahek Gulani; Amarae Ferguson; Mohammad Uddin; Susu M. Zughaier; Martin J. D’Souza (Pharmaceutics)
Background: Influenza virus is one of the major respiratory virus infections that is a global health concern. Although there are already approved vaccines, most are administered via the intramuscular route, which is usually painful, leading to vaccine hesitancy. To this end, exploring the non-invasive, transdermal vaccination route using dissolving microneedles would significantly improve vaccine compliance. Research on innovative vaccine delivery systems, such as antigen-loaded PLGA microparticles, has the potential to pave the way for a broader range of vaccine candidates. Methods: In this proof-of-concept study, a combination of the inactivated influenza A H1N1 virus and inactivated influenza A H3N2 virus were encapsulated in a biodegradable poly (lactic-co-glycolic acid) (PLGA) polymeric matrix within microparticles, which enhanced antigen presentation. The antigen PLGA microparticles were prepared separately using a double emulsion (w/o/w), lyophilized, and characterized. Next, the vaccine microparticles were assessed in vitro in dendritic cells (DC 2.4) for immunogenicity. To explore pain-free transdermal vaccination, the vaccine microparticles were loaded into dissolving microneedles and administered in mice (n = 5). Results: Our vaccination study demonstrated that the microneedle-based vaccine elicited strong humoral responses as demonstrated by high antigen-specific IgA, IgG, IgG1, and IgG2a antibodies in serum samples and IgA in lung supernatant. Further, the vaccine also elicited a strong cellular response as evidenced by high levels of CD4+ and CD8a+ T cells in lymphoid organs such as the lymph nodes and spleen. Conclusion: The delivery of influenza vaccine-loaded PLGA microparticles using microneedles would be beneficial to individuals experiencing needle-phobia, as well as the geriatric and pediatric population.